2012
DOI: 10.1118/1.4747266
|View full text |Cite
|
Sign up to set email alerts
|

Differences in predicted and actually absorbed doses in peptide receptor radionuclide therapy

Abstract: Purpose: An important assumption in dosimetry prior to radionuclide therapy is the equivalence of pretherapeutic and therapeutic biodistribution. In this study the authors investigate if this assumption is justified in sst2‐receptor targeting peptide therapy, as unequal amounts of peptide and different peptides for pretherapeutic measurements and therapy are commonly used. Methods: Physiologically based pharmacokinetic models were developed. Gamma camera and serum measurements of ten patients with metastasizin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
60
1
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(70 citation statements)
references
References 53 publications
(61 reference statements)
4
60
1
1
Order By: Relevance
“…The radiochemical state and biological processes responsible for the observed spatial redistribution of activity is likely to change with time after injection. Given the limited amount of available input data and the additional model parameters that would be required, we did not include effects of receptor-mediated saturable uptake, protein degradation and formation of radioactive metabolites (Kletting et al 2012). Hence, the physiological interpretation and general applicability of the PK model should not be overstated.…”
Section: Discussionmentioning
confidence: 99%
“…The radiochemical state and biological processes responsible for the observed spatial redistribution of activity is likely to change with time after injection. Given the limited amount of available input data and the additional model parameters that would be required, we did not include effects of receptor-mediated saturable uptake, protein degradation and formation of radioactive metabolites (Kletting et al 2012). Hence, the physiological interpretation and general applicability of the PK model should not be overstated.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the previously developed model (9), the binding of peptide to serum proteins was explicitly modeled to adequately describe serum activity for time points greater than 24 h.…”
Section: Pbpk Model Structurementioning
confidence: 99%
“…The effect of peptide amount was investigated in animal studies (4,5). In humans, a strong effect of substance amount on the therapeutic index has been observed in previous work with monoclonal antibodies (6)(7)(8) but also peptides (9,10). Sabet et al showed that saturation of tumor-binding sites requires considerably higher amounts of peptide than for those in normal tissue (10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…90 Y is a pure β-emitter, whose physical half-life is 64 h. The energy of the released β-particles is up to 2.28 MeV, range of beta particles in soft tissues is short, consequently killing the cells near the point of emission. However, in this type of procedure, a significant amount of 90 Y decays in other organs, causing unwanted irradiation of healthy tissue [4,5].…”
Section: Introductionmentioning
confidence: 99%